1999
DOI: 10.1080/027868299304435
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Intercomparison of Filter-Based Measurements of Visible Light Absorption by Aerosols

Abstract: ABSTRACT. Data on light absorption by atmospheric particles are scarce relative to the need for global characterization. Most of the existing data come from methods that measure the change in light transmission through a lter on which particles are collected. We present a calibration of a recently developed lter-based instrument for continuous measurement of light absorption (model PSAP, Radiance Research, Seattle, WA) that has been incorporated in several measurement programs. This calibration uses a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
1,271
6
9

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 978 publications
(1,313 citation statements)
references
References 31 publications
27
1,271
6
9
Order By: Relevance
“…Bond et al reported that even nonabsorbing particles can increase light extinction when deposited on the filter via light scattering. 36 This effect resulted in a 2-9% increase in optical density at atmospheric concentrations. Bond et al also reported that scattering of non-absorbing aerosols mixed with the absorbing aerosols can increase light extinction by 20-30%.…”
Section: Interferencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Bond et al reported that even nonabsorbing particles can increase light extinction when deposited on the filter via light scattering. 36 This effect resulted in a 2-9% increase in optical density at atmospheric concentrations. Bond et al also reported that scattering of non-absorbing aerosols mixed with the absorbing aerosols can increase light extinction by 20-30%.…”
Section: Interferencesmentioning
confidence: 99%
“…Light scattering may have more of an influence if other scattering aerosols are collected with the DPM. 36 The Airtec device (see Fig. 1) weighs approximately 1.5 lbs and can be worn by a worker or positioned for area sampling.…”
Section: Description Of Airtecmentioning
confidence: 99%
See 3 more Smart Citations